Development of Employer Brand Evaluation Scale Based on Computer Data Mining and Its Relationship with College Students' Job-Hunting Intention. (6th May 2022) - Yang, Guilin; Yang, Wanping; Yang, Guihua
Abstract : The inclinations among employees are changed because of the evolutions in the twenty-first century's workplace. It is consequently critical to decide the elements that workers look for in an organization and their goal conduct to stop from their occupation to work on the issues of high wearing down that occurs in an organization. This study determines the connection between employer branding and turnover intention among employees. Data mining and factor analysis methods are used to extract public factors, design a more concise employer brand evaluation system, and develop a new employer brand evaluation scale. The relationship between the various dimensions of employer brand in China's banking industry and college students' job-hunting intentions are examined. Results show that contemporary college student job-seekers in China pay more attention to short-term and directly experienced security and experiential needs. It ignores the long-term and hard-to-feel self-realization needs and respect needs in the short term. These dimensions reflect the perceptions of existing employees regarding their organization. The scale is found to be statistically sound for measuring the employer brand.